PERANAN BRIGADE MOBILE DALAM MEMPERTAHANKAN KEMERDEKAAN INDONESIA TAHUN 1946-1949 - Agung Nugraha; Agus Mulyana; Achmad Iriyadi (Universitas Pendidikan Indonesia dan APPS (Asosiasi Pendidik dan Peneliti Sejarah), 2018)
This research is entitled “The Role of Mobile Brigade Corps in Defending the Independence (19461949)”. The researcher chose this problem because Mobile Brigade Corpse was the main pioneer in defending the independence. At the time of defending the independence, this Mobile Brigade Corps was not disbanded by Japan so that the Mobile Brigade Corps was really essential in defending Indonesia’s independence. The main problem of this research is “How were the role of Mobile Brigade Corps in defending the independence?” The method used is the method of historical research by doing four steps of research which are heuristic, criticism, interpretation, and historiography. The technique used in data collection is literature study by reviewing the sources of literature relevant to the issues studied. Based on the research results, it can be explained that: First, before the independence, there is a change in the role performed by Mobile Brigade Corps. In the time of the Dutch colonialism, the role of the Mobile Brigade Corps was to maintain security and order but during the Japanese colonialism the role of Mobile Brigade Corpse is combat troops in helping Japan to face the Allies. Second, the early days of independence were marked by Japan’s surrender to the Allies. After Japan surrendered to the Allies, all Japanese-formed military organizations were disbanded except the Mobile Brigade Corps. Under that condition, the Mobile Brigade Corpse joined the Indonesian republic. After joining the Indonesian republic, the role of the Mobile Brigade Corps was to disarm Japan along with the people. The disarmament results are then distributed to the struggle agencies. When entering the period of defending the independence, the role of the Mobile Brigade Corps is to fight against the threat of the Allies and the Netherlands. The resistance was carried out by the Mobile Brigade Corps along with other struggling agencies such as the People’s Security Army.